Therapeutic Potential of Tadalafil in Doxorubicin-Induced Pulmonary and Hematological Toxicities in Wistar Rats (Nigerian Journal of Physiological Sciences, 2025)
Doxorubicin (DOX) therapy is associated with pulmonary toxicity and hematotoxicity as its off-target side-effects. In this study, tadalafil (TAD) was investigated for its chemopreventive potential against DOX-induced pulmonary toxicity and hematotoxicity in 48 male Wistar rats that were divided into 8 groups of 6 rats/group and orally pretreated with 2.5 mg/kg/day, 5.0 mg/kg/day, and 10 mg/kg/day TAD 1 hour before intraperitoneal injection of 2.5 mg/kg DOX on alternate days for 12 days after which the rats were humanely sacrificed. Blood samples for hematological and biochemical endpoints and lung tissue samples for oxidative stress markers, pro-inflammatory cytokines assay and for histopathology were collected. The rats body weights at the start and end of the experiments were measured. Results showed that DOX toxicity was associated with significant (p